EVALUASI PERENCANAAN TEBAL PERKERASAN LENTUR DENGAN METODE BINA MARGA 2002 DAN BINA MARGA 2017 - Selvianti, Riska; Dewi, Selpa; Yermadona, Helga (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Road conditions damaged on Jalan Belubus include potholes, patches, cracked crocodile skin, loose granules, cracked edges, thus disturbing the comfort and safety of road users. In this research, 2 methods are used to calculate the thickness of flexible pavement, namely the Bina Marga 2002 method and the Bina Marga 2017 method. In the 2002 Bina Marga calculation method, it was found that the thickness of the layer D1 = 5 cm, D2 = 15 cm, and D3 = 38 cm with a RAB of IDR 2,580,642,372.00. Meanwhile, in the 2017 Bina Marga calculation method, the AC WC layer = 4 cm, AC BC = 6 cm, AC Base = 10.5 cm, and LPA class A = 30 cm with a RAB worth IDR 2,382,747,906.00. Keywords: Flexible Pavement; Bina Marga 2002; Bina Marga 2017.